Answer:
=4.15n + 2.98
Step-by-step explanation:
Answer:
x can be transformed into -1/2x
-1/2x / -1/2=x
1/-1/2=-2
x>-2
Step-by-step explanation:
Tell me if it’s too confusing or if you got it hope it help sorry if it didn’t
Answer:
6x-8
Step-by-step explanation:
you multiply 2*3x=6x then 4*2=8
therefore 6x-8=(3x-4)2
Answer:
k = 48
For x = 6, y = 8.
Step-by-step explanation:
The general equation for inverse variation is
y = k/x
We are told that y = 24 when x = 2, so we plug in those two values in the general equation to find the value of k.
24 = k/2
k = 24 * 2 = 48
Now that we know k = 48, the equation for our case is
y = 48/x
Now we plug in x = 6 and find y.
y = 48/x
y = 48/6
y = 8
Answer:
x = - 90
Step-by-step explanation:
Given
10x + 60 = 9x - 30 ( subtract 9x from both sides )
x + 60 = - 30 ( subtract 60 from both sides )
x = - 90